2015
DOI: 10.3233/nre-151237
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive brain stimulation for Parkinson’s disease: Current concepts and outlook 2015

Abstract: Abstract. BACKGROUND AND PURPOSE:In advanced Parkinson's disease (PD), the emergence of symptoms refractory to conventional therapy poses a therapeutic challenge. The success of deep brain stimulation (DBS) and advances in the understanding of the pathophysiology of PD have raised interest in non-invasive brain stimulation as an alternative therapeutic tool. The rationale for its use draws from the concept that reversing abnormalities in brain activity and physiology thought to cause the clinical deficits may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 131 publications
(179 reference statements)
0
28
0
1
Order By: Relevance
“…Our findings clearly favor the concept that LKA accounts for dexterous impairment beyond parkinsonian symptoms, a controversial debate that started a decade ago. 19,20 Because dopaminergic treatment only minimally improves LKA, 1 nonpharmacologic treatment options, such as noninvasive, repetitive brain-stimulation techniques 21,22 or specific home-based dexterity training, 23 may offer an improvement in dexterous functions for patients with PD.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings clearly favor the concept that LKA accounts for dexterous impairment beyond parkinsonian symptoms, a controversial debate that started a decade ago. 19,20 Because dopaminergic treatment only minimally improves LKA, 1 nonpharmacologic treatment options, such as noninvasive, repetitive brain-stimulation techniques 21,22 or specific home-based dexterity training, 23 may offer an improvement in dexterous functions for patients with PD.…”
Section: Discussionmentioning
confidence: 99%
“…As highlighted by Benninger and Hallett (2015), the shortcomings of conventional pharmacological therapy coupled with the recent success of deep brain stimulation in advanced PD has raised interest in non-invasive forms of neuro-stimulation, however, there has so far been little evidence from transcranial studies that the reported gains translate to long-lasting improvements in well-being and functional independence. We recognize that the inferential power of the present single-case study is limited, however, the improved response profile demonstrated by the participant, perhaps most notably at 5months follow-up, alludes to a practical patient benefit that, in our opinion, justifies larger-scale investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence shows that stimulation of specific brain areas with non-invasive brain stimulation (e.g. transcranial magnetic stimulation (TMS) or transcranial direct current stimulation (tDCS)) can be used as a supplementary therapeutic option to enhance training benefits (Benninger & Hallett, 2015;Buch et al, 2017). Pairing tDCS with a biologically relevant stimulus (i.e.…”
Section: Introductionmentioning
confidence: 99%